Bibliographic Analysis of Scientific Research on Downy Mildew (Pseudoperonospora humuli) in Hop (Humulus lupulus L.) - Marcia Magalhães de Arruda; Fabiana da Silva Soares; Marcelle Teodoro Lima; Eduardo Lopes Doracenzi; Pedro Bartholo Costa; Duane Nascimento Oliveira; Thayse Karollyne dos Santos Fonsêca; Waldir Cintra de Jesus Junior; Alexandre Rosa dos Santos (Agriculture, 2024)
This study focused on downy mildew in hop caused by the pathogen Pseudoperonospora humuli. A systematic literature review was conducted using bibliometric analysis to explore trends in publishing, prominent research themes, and where research is being conducted on hop downy mildew. The databases Scopus, Web of Science, and ScienceDirect were used to identify publications spanning from 1928 to 2023. The analysis yielded 54 publications, with the most cited studies primarily focusing on disease management and host resistance. Additionally, these studies explored the genetic and pathogenic relationship between P. cubensis and P. humuli. A word co-occurrence map revealed that the main themes addressed in the publications included “hop”, “disease”, “downy”, “humuli”, “mildew”, and “Pseudoperonospora”. Notably, there was a particular emphasis on subtopics such as disease management, the disease reaction of hop cultivars, and the influence of weather factors on hop downy mildew. Notably, there was limited knowledge about the disease in regions with tropical climates. This study provides valuable information that can support and guide future research endeavors concerning downy mildew in hop cultivation.